WGV: An Australian Urban Precinct Case Study to Demonstrate the 1.5 °C Agenda Including Multiple SDGs - Wiktorowicz, J.; Babaeff, T.; Breadsell, J.; Byrne, Joshua; Eggleston, J.; Newman, Peter (Cogitatio, 2018)
The WGV project is an infill residential development in a middle suburb of Perth, Western Australia. Its urban planning innovation is in its attempt to demonstrate net zero carbon as well as other sustainability goals set by urban planning processes such as community engagement and the One Planet Living accreditation process. It is a contribution to the IPCC 1.5 °C agenda which seeks to achieve deep decarbonization while also delivering the UN Sustainable Development Goals (SDGs). Solar photovoltaics and battery storage are incorporated into the development and create net zero carbon power through an innovative ‘citizen utility’ with peer-to-peer trading. The multiple sustainable development features such as water sensitive design, energy efficiency, social housing, heritage retention, landscape and community involvement, are aiming to provide inclusive, safe, resilient and sustainable living and have been assessed under the SDG framework.